Kesesuaian Lahan Jenis Tanaman Kehutanan Pada Areal Lahan Terbuka Di Kawasan Hutan Pendidikan Gunung Walat (Hpgw), Sukabumi Jawa Barat - Supriyanto Supriyanto; Muhammad Hasan Sayid (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2022)
Gunung Walat Education Forest is a Special Purpose Forest for Education. At present many areas have lost their vegetation cover (trees) or become opened areas in the GWEF area. Land suitability by looking at topography, soil and climate factors needs to be done to find out the type of forestry plant that is suitable for planting on the open areas. Stages of land suitability, is consisted of image processing, visual interpretation of satellite imagery, ground checks, soil and litter observations, data collection on soil physical and chemical properties and climate, land characteristic observations, and matching processes. The results of matching with Liebeg's minimum law and scoring system showed that eucalypt (E. grandis), sengon (F. moluccana), caliandra (C. calothyrsus), mahagoni (S. mahagoni), pine (P. merkusii), lamtoro (F. moluccana), cajuput (M. leucadendron), damar (A. loranthifolia), acacia (A. auriculiformis), and rasamala (A. excelsa) are suitable for planting in open areas in the Gunung Walat Education Forest (GWEF). While teak (T. grandis) is not suitable for planting in opened areas in the GWEF. Keywords: Forest tree, GWEF, land suitability, opened area.